Syphacia sp. (Spirurida: Oxyuridae) parasitizing the rodent Graomys griseoflavus (Waterhouse, 1837) (Rodentia: Cricetidae) in San Juan province, Argentina - Castillo, Gabriel N. (2025)
Nematodes of the genus Syphacia sp. (family Oxyuridae) parasitize the cecum of rodents belonging to the families Cricetidae, Muridae and Sciuridae. This study reports for the first time the presence of Syphacia sp. in San Juan province and expands the knowledge about its parasitism in the rodent Graomys griseoflavus (Waterhouse, 1837), both at provincial and national level. These observations constitute a novel contribution to the knowledge of the helminthofauna associated with G. griseoflavus in San Juan and Argentina.